Involvement of the Transcriptional Coactivator ThMBF1 in the Biocontrol Activity of Trichoderma harzianum - Rubio, M. Belén; Pardal, Alonso J.; Cardoza, Rosa E.; Gutiérrez, Santiago; Monte, Enrique; Hermosa, Rosa (Frontiers in Microbiology, 2017)
Trichoderma harzianum is a filamentous fungus well adapted to different ecological niches. Owing to its ability to antagonize a wide range of plant pathogens, it is used as a biological control agent in agriculture. Selected strains of T. harzianum are also able to increase the tolerance of plants to biotic and abiotic stresses. However, little is known about the regulatory elements of the T. harzianum transcriptional machinery and their role in the biocontrol by this species. We had previously reported the involvement of the transcription factor THCTF1 in the T. harzianum production of the secondary metabolite 6-pentyl-pyrone, an important volatile compound related to interspecies cross-talk. Here, we performed a subtractive hybridization to explore the genes regulated by THCTF1, allowing us to identify a multiprotein bridging factor 1 (mbf1) homolog. The gene from T. harzianum T34 was isolated and characterized, and the generated Thmbf1 overexpressing transformants were used to investigate the role of this gene in the biocontrol abilities of the fungus against two plant pathogens. The transformants showed a reduced antifungal activity against Fusarium oxysporum f. sp. lycopersici race 2 (FO) and Botrytis cinerea (BC) in confrontation assays on discontinuous medium, indicating that the Thmbf1 gene could affect T. harzianum production of volatile organic compounds (VOC) with antifungal activity. Moreover, cellophane and dialysis membrane assays indicated that Thmbf1 overexpression affected the production of low molecular weight secreted compounds with antifungal activity against FO. Intriguingly, no correlation in the expression profiles, either in rich or minimal medium, was observed between Thmbf1 and the master regulator gene cross-pathway control (cpc1). Greenhouse assays allowed us to evaluate the biocontrol potential of T. harzianum strains against BC and FO on susceptible tomato plants. The wild type strain T34 significantly reduced the necrotic leaf lesions caused by BC while plants treated with the Thmbf1-overexpressing transformants exhibited an increased susceptibility to this pathogen. The percentages of Fusarium wilt disease incidence and values of aboveground dry weight showed that T34 did not have biocontrol activity against FO, at least in the ‘Moneymaker’ tomato variety, and that Thmbf1 overexpression increased the incidence of this disease. Our results show